PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN PERAN GURU TERHADAP PRESTASI PESERTA DIDIK DI SMPN 35 DAN SMPN 44 DI KECAMATAN MIJEN KOTA SEMARANG - Siregar, Yolanda Fricillia; Sulandari, Susi; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The purpose of this study was to determine: (1) description of student achievement, principal managerial abilities and teacher roles; (2) the magnitude of the influence of the principal's managerial ability on student achievement; (3) the magnitude of the influence of the teacher's role on student achievement; and (4) the magnitude of the influence of managerial ability and the role of teachers on student achievement in public junior high school in Mijen Sub District. This research is a quantitative explanatory research. The population in this study were students at SMPN 35 and SMPN 44, with a total sample of 74 people. Data analysis techniques to determine the principal managerial ability, the role of teachers and student achievement used descriptive statistical analysis and to determine the magnitude of the influence of the principal managerial ability variables and the role of teachers on student achievement were processed using Kendall tau correlation analysis technique with the help of SPSS IBM 23. The results of this study indicate the following: (1) The achievement of students in the Poor category with a value of 2,41, the managerial ability of the principal in the Very Good category with a value of 3,52 and the role of the teacher in the Good category with a value of 2,66 ; (2) Managerial ability has a correlation to student achievement by 0,265 (3) The role of the teacher has a correlation with student achievement by 0,390 and (4) Managerial ability of school principals and the role of teachers together have a correlation with student achievement students of 0,718.